An improved ethanol microfluidic fuel cell based on a PdAg/MWCNT catalyst synthesized by the reverse micelles method. (1st March 2016) - Armenta-González, A.J.; Carrera-Cerritos, R.; Moreno-Zuria, A.; Álvarez-Contreras, L.; Ledesma-García, J.; Cuevas-Muñiz, F.M.; Arriaga, L.G.
Graphical abstract: Highlights: Pd and PdAg catalysts were prepared by microemulsion method, the electrocatalysts had between 4 and 7 nm sizes. PdAg/MWCNT catalyst with improved performance for ethanol oxygen reaction was obtained in comparison with Pd/MWCNT. An air-breathing microfluidic fuel cell is presented using high concentration of ethanol (3 M). Abstract: In this work, two electrocatalysts based on Pd (Pd/MWCNT and PdAg/MWCNT) were synthesized using reverse micelles for ethanol oxidation (EOR), and evaluated in an air-breathing microfluidic fuel cell. Commercial Pd (Pd/C) was used for comparison. The average nanoparticle size estimated by TEM was approximately 4–7 nm for both electrocatalysts. TGA measurements indicated that the electrocatalysts had similar metallic loading (19% for Pd and 17% for PdAg). The materials were tested for EOR in 1 M KOH. Fuel cell tests were performed in an air-breathing microfluidic fuel cell (ABμFFC) in which oxygen was obtained from the air to improve the performance of the cathodic reaction. The results were compared with those obtained using a closed microfluidic fuel cell (μFFC). In these devices, two streams were injected, one containing fuel and the other containing an electrolyte solution (1 M KOH), and commercial Pt (Pt/C) was used as cathodic catalyst. The ABμFFC that used the PdAg/MWCNT electrocatalyst performed better (almost 70% more power was harvested) than the one that used the Pd/MWCNT electrocatalyst. Finally, the power density harvested from the ABμFFC was 4 times higher than that harvested from the μFFC.